Parental Attitudes and Perceptions Towards Vaccines - Gundogdu, Zuhal (Cureus, 2020)
Objective Success of any vaccination program and uptake of children's vaccines largely depends upon the parents' perceptions and attitudes. This study provides a snapshot of parents' views towards vaccines included in the nationally-funded vaccination program, together with two unfunded vaccines in Kocaeli, Turkey. Methods Data were gathered from a convenience sample through a questionnaire that explored the socio-demographic factors of the parents and the vaccination status of their children. The survey content was based on Health Belief Model. Mann-Whitney test was used for comparisons as there is no prior information regarding data distribution and the dependent variable is represented on an ordinal scale. Out of 300 parents who brought their children into the pediatrics polyclinics, 262 parents responded positively and took part. The questionnaires were filled out by mothers alone 67.6 % (n=177), 28.6 % (n=75) by fathers and mothers (both present), 3.1% (n=8) by fathers alone and the remaining 0.8% (n=2) were filled by other relatives. Results While the majority of diseases prevented by the vaccines were perceived to be serious, pneumococcal infection and chickenpox were considered to be less serious and there was no strong opinion for the rotavirus vaccine. The main reasons that influenced parents' decisions towards unfunded vaccines were advice from a pediatrician and the cost. Lastly, demographic factors such as family income, mothers' education and job types of mothers were important in contrast to previously published studies. Conclusions The acceptance of a new vaccine depends on a complex interaction of factors, but parents' perceptions may vary considerably. The main factors influencing parental acceptance are the availability of information and the cost. Therefore, for a new vaccination program to succeed, it should be funded by the government and a specific public health education program should be undertaken.